Optimizing the Citra Raya Conservation Lake as Raw Material for Clean Water Treatment in the Citra Raya Residential Area, Tangerang - Suprapti S.; Vebruara Ringgo; Hidayat Acep; Isradi Muhammad; Firdaus Hendy Yusman (BIO Web of Conferences)
In Tangerang Indonesia, the Citra Raya residential area, three Citra Raya Conservation Lakes function as sources of clean water production. The area is flooded when the lake overflows during the rainy season. Community access to clean water is disrupted throughout the dry season due to a decrease in clean water discharge. So an effort is needed to increase the sustainability of its availability in achieving sustainable development goals (SDGs). This research was conducted to determine the water balance and improve water management in the three lakes. The water demand study was carried out based on the number of active consumers in 2020 and predictions until 2025. Flow characteristics and a basic planning-month approach were used to analyze water availability. Water balance analysis is used to compare the availability of reliable discharge and its needs as a basis for optimization. Optimization using linear programming. Optimization results show that the availability of raw water in the conservation lake is sufficient to meet the clean water demand of the Citra Raya area every month. However, in reality, there are problems such as pipe leaks and legal violations. This requires further research.